Democratic Liberal Theory Based on Literature Review - Iskandarsyah Siregar (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2023)
Since the emergence of the application of the idea of democracy as the system of choice, various groups have complained about the evil practices of democratic politics. One of the shooting targets is that we choose the wrong one, namely adopting the model of the majority or liberal democracy. In the literature on democratic theory, one of the relevant theories for improving democratic practice is TDD (Theory of Deliberative Democracy). Although still using the principle of representation, TDD in general makes corrections or improvements to the procedures and substance of democracy which have so far been poorly practiced in Indonesia. This research is qualitative research using a descriptive-analytic method to provide a clear picture of the object of the problem. The conclusion of this study shows evidence of the existence of a democratic model both in substance and procedure. In contrast to the representative mechanism which was originally derived from the theory of representative democracy. There is visible hypocrisy and inconsistency in the implementation of democracy, which has never been considered a complete system.